Prosperity for All Saotomeans : Priorities to End Poverty, Promote Growth, and Build Resilience in São Tomé and Príncipe - World Bank (World Bank, Washington, DC, 2021)
São Tomé and Príncipe (STP), a small island nation of 215,000 people in the Gulf of Guinea off the coast of Central Africa, is in many ways a country of great untapped wealth. One of Africa’s least known countries, its striking volcanic landscape is home to virgin rainforests with rich biodiversity, while its large exclusive economic zone (EEZ), approximately 160 times larger than the archipelago, is a marine biodiversity hotspot and supports high numbers of species unique to the area. It has among the lowest violence and crime rates in Africa and has had peaceful elections and transitions of power since becoming a multiparty democracy in 1991, making it an outlier in the region. It also has a young population, half of which is under 18 years of age, raising the prospect of a demographic dividend to be tapped in the years ahead. Its economy has grown steadily over the past two decades, outpacing its high population growth. This growth reflects strong inflows of overseas development aid (ODA) and revenues from oil exploration that have enabled the government to expand public investments, particularly in infrastructure, social protection, health, and education. This has enabled STP to bridge the gap caused by years of underinvestment in local human and physical capital, a legacy of the country’s colonial past (its first secondary school was established only in 1952). This growth model has not been able to spark the fundamental changes needed for the economy to generate resilient poverty reduction and shared prosperity. Few jobs are being created, and indicators and consultations with civil society reveal a broad sense of social exclusion even as the economy has grown. This model is not sustainable.A new growth model is needed, one that will be able to provide more opportunities for its growing population. In the context of STP, a small nation with low capacity facing increasing vulnerabilities and in need of a new growth model, it is important to think strategically to identify an effective way forward. To this end, this Systematic Country Diagnostic (SCD) identifies the most critical vulnerabilities and constraints facing the country and, from these, a set of actionable priorities that will contribute to reducing poverty while promoting sustainable growth and shared prosperity.